Letter : German activities in the Basque Country - Gondra, A. de
012b-0055-001 J.I. de Lizaso Delegate of the Basque Government. 14 Eccleston Square London S.W.1 Tel Victoria 0926. January 31st., 1939 The Assistant Secretary, TRADES UNION CONGRESS, Transport House Smith Square, LONDON S.W.1 Dear Sir, GERMAN ACTIVITIES IN THE BASQUE COUNTRY I want to thank you for your letter of January 30th and also your offer to pass on the information we sent you to the British Government. The information in question was in fact communicated to the British Authorities; nevertheless, we want to express our appreciation of your kind offer. Yours sincerely, Angel de Gondra Secretary 292/946/12b/55